The Noninvasive Urinary Polyomavirus Haufen Test Predicts BK Virus Nephropathy in Children After Hematopoietic Cell Transplantation: A Pilot Study. Issue 10 (October 2016) - Laskin, Benjamin L.; Singh, Harsharan K.; Beier, Ulf H.; Moatz, Taylor; Furth, Susan L.; Bunin, Nancy; Witte, David; Goebel, Jens; Davies, Stella M.; Dandoy, Christopher; Jodele, Sonata; Nickeleit, Volker
Abstract : Background: After hematopoietic cell transplantation (HCT), polyoma-BK virus is associated with hemorrhagic cystitis and also with polyomavirus nephropathy (PVN). However, the true burden of post-HCT PVN is unknown because kidney biopsies are avoided due to their bleeding risk. The novel, noninvasive urinary PV-Haufen test detects PVN in kidney transplant recipients with greater than 95% positive/negative predictive values. We hypothesized that the detection of PV-Haufen in voided urine samples—a positive PV-Haufen test—was also clinically significant after HCT. Methods: We examined 21 suitable urine samples from 14 patients (median age, 15 years; 71.4% male) who were selected from repositories for having varying degrees of BK viremia (range, 0-1.0 × 10 8 copies/mL), hemorrhagic cystitis (present/absent), and data on kidney function. Urine samples were obtained at a median of 88 days post-HCT. Results: The PV-Haufen were detected in 5 of 14 patients (35.7%) and 7 of 21 (33.3%) urine samples, with histologic confirmation of PVN in 1 autopsy specimen. After a median of 285 days post-HCT, patients with PV-Haufen had an increased risk of dialysis-dependent renal failure ( P < 0.05). All 3 dialysis-dependent patients had PV-Haufen and died. The presence of urinary PV-Haufen was not significantly correlated with hemorrhagic cystitis. From the 16 urines collected during BK viremia, 43.8% were PV-Haufen–positive, and 56.2% were negative. The PV-Haufen were not present in the 5 urines from patients without concomitant BK-viremia. Conclusions: In this proof-of-concept study, a positive PV-Haufen test was only seen in some patients with BK viremia and was not associated with hemorrhagic cystitis. The detection of PV-Haufen suggests underlying PVN with an increased risk of kidney failure and dialysis. Abstract : This study shows that use of electron microscopy of urine samples to detect Haufen-bodies in hematopoietic stem cell patients with BK viremia can be used to help diagnose BK nephropathy noninvasively. This technique may be useful in solid organ transplantation. Supplemental digital content is available in the text.